Chemosensitivity of U251 Cells to the Co-treatment of D-Penicillamine and Copper: Possible Implications on Wilson Disease Patients - Katerji, Meghri; Barada, Kassem; Jomaa, Mustapha; Kobeissy, Firas; Makkawi, Ahmad-Kareem; Abou-Kheir, Wassim; Usta, Julnar (Frontiers in Molecular Neuroscience, 2017)
D-Penicillamine (PA), a copper chelator, and one of the recommended drugs for treatment of Wilson disease (WD) has been reported to worsen the symptoms of patients with neurologic presentations. However, the cause of this paradoxical response has not been fully elucidated and requires further investigations. Accordingly, we have studied the in vitro effect of Cu and /or PA treatment on human glioblastoma U251 cells as an in vitro model of Cu cytotoxicity. Treatment of U251 cells with either Cu or PA exerted no significant effect on their morphology, viability or ROS level. In contrast, co-treatment with Cu-PA caused a decrease in viability, altered glutathione and ceruloplasmin expression coupled with marked increase in ROS; depolarization of mitochondrial membrane potential; and an increase in Sub G0 phase; along with alpha-Fodrin proteolysis. These findings along with the absence of LDH release in these assays, suggest that combined Cu-PA exposure induced apoptosis in U251 cells. In addition, pre- /or co-treatment with antioxidants showed a protective effect, with catalase being more effective than N-acetyl cysteine or trolox in restoring viability and reducing generated ROS levels. By comparison, a similar analysis using other cell lines showed that rat PC12 cells were resistant to Cu and/or PA treatment, while the neuroblastoma cell line SH-SY5Y was sensitive to either compound alone, resulting in decreased viability and increased ROS level. Taken together, this study shows that glioblastoma U251 cells provide a model for Cu-PA cytotoxicity mediated by H2O2. We postulate that PA oxidation in presence of Cu yields H2O2 which in turn permeates the plasma membrane and induced apoptosis. However, other cell lines exhibited different responses to these treatments, potentially providing a model for cell type- specific cytotoxic responses in the nervous system. The sensitivity of different neural and glial cell types to Cu-PA treatment may therefore underlie the neurologic worsening occurring in some PA-treated WD patients. Our results also raise the possibility that the side effects of PA treatment might be reduced or prevented by administering antioxidants.